2021
DOI: 10.7759/cureus.20604
|View full text |Cite
|
Sign up to set email alerts
|

Current Advances in Immunotherapy for Glioblastoma Multiforme and Future Prospects

Abstract: Glioblastoma is the most frequent and malignant type of brain tumor. It has a reputation for being resistant to current treatments, and the prognosis is still bleak. Immunotherapies have transformed the treatment of a variety of cancers, and they provide great hope for glioblastoma, although they have yet to be successful. The justification for immune targeting of glioblastoma and the obstacles that come with treating these immunosuppressive tumors are reviewed in this paper. Cancer vaccines, oncolytic viruses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…As aforementioned, the cooperation of the innate and adaptive immune systems is crucial in oncolytic virotherapy response, and matching it with other immunotherapy strategies such as checkpoint inhibitors increases the immunological response and tumor regression[ 140 - 142 ].…”
Section: Oncolytic Virusesmentioning
confidence: 99%
See 3 more Smart Citations
“…As aforementioned, the cooperation of the innate and adaptive immune systems is crucial in oncolytic virotherapy response, and matching it with other immunotherapy strategies such as checkpoint inhibitors increases the immunological response and tumor regression[ 140 - 142 ].…”
Section: Oncolytic Virusesmentioning
confidence: 99%
“…However, the results were not as significant as expected in survival and remission rate, in human trials[ 146 ]. Besides that many adverse effects have been found such as seizures, edema, thrombocytopenia and pulmonary embolism, and these complications when coupled with the fact that not all GBM patients express EGFRvIII, become a limitation for this therapy, since not all patients could use this vaccine[ 140 ].…”
Section: Vaccine-based Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Nivolumab, an anti-PD-1 mAb that was also approved for use by the US FDA in 2014 as well, was assessed as a treatment for recurrent or metastatic squamous-cell carcinoma of the head and neck [ 20 ], advanced renal-cell carcinoma [ 38 ], and nonsquamous NSCLC [ 39 ]. Additionally, it works on Glioblastoma Multiforme since the PD-L1 protein is abundant on its surface [ 40 ]. A lot of randomized clinical trials indicated that NSCLC patients who were treated combination with nivolumab with pembrolizumab showed higher overall survival than those treated with docetaxel [ 41 ].…”
Section: Monoclonal Antibodies (Mabs)mentioning
confidence: 99%